Investigating Neurogenic Differentiation of Dental Pulp Stem Cells Using PLA and Graphene Thin-Film and Electrospun Fiber Scaffolds in Vitro. (2020) - Mehta, Dipen; Stabile, Michael; Stabile, Nicholas; Luo, Daniel; Feng, Kuan-Che; Simon, Marcia; Rafailovich, Miriam
ABSTRACT: Dental pulp derived cells are pluripotent stem cells which can be differentiated along odontogenic, osteogenic, adipogenic, or neurogenic lineages. Odontogenic and osteogenic differentiation, in the absence of dexamethasone, have been shown to be highly dependent on substrate morphology and mechanics. Here we focus on neurogenic differentiation, using the protocol described by A. Arthur et al., and its dependence on substrate nature. DPSCs were cultured on PLA, a biodegradable polymer approved for internal use. The upregulation of genetic markers was compared with that of cells plated on standard TCP. The role of substrate morphology was investigated by plating on electrospun fibers approximately 2.0 ± 1.0 μm in diameter and on spin-cast thin films. The influence of graphene was investigated through the addition of 3% and 10% graphene nanoparticles to the films and fibers respectively. The aspect ratio of the cells was measured using confocal microscopy. Cells grown on graphene containing substrates had larger aspect ratios than their non-graphene counterparts, and cells grown on microfibers were longer than their counterparts on the flat films. But the cell aspect ratio did not necessarily correlate with genetic differentiation. The results after 21 days of incubation indicated that early markers (TBP, β-III tubulin), decreased uniformly on all substrates relative to day 0, with the largest decrease occurring on the PLA flat film with graphene. The late stage marker, NEFM, which indicates differentiation, was upregulated to a significantly larger extent on all PLA substrates. No difference was observed between the fibers and the flat film in the absence of graphene, thus morphology did not play a significant role on this polymer. Addition of graphene did not affect the outcome on the fibers, but significantly suppressed the gene expression on the flat films. These results indicate that PLA is a promising scaffold material for neurogenic differentiation.